“FBT Is for the Rich”: A Qualitative Study Examining Clinicians' Experiences and Perceptions of Treatment Access and Engagement for Diverse Families in Family‐Based Treatment - Sauerwein, Jessica; Austin, Amelia; Singh, Manya; Pedram, Pardis; Allan, Erica; Bruett, Lindsey; Eckhardt, Sarah; Forsberg, Sarah; Keery, Helene; Kimber, Melissa; Pradel, Martin; Accurso, Erin C.; et al. (The International journal of eating disorders, 2025)
ABSTRACT Objective Family‐based treatment (FBT) is the leading evidence‐based treatment for adolescent eating disorders, but research exploring access and engagement in FBT is sparse. This paper focuses on findings from a broader study, specifically addressing the social determinants of health (SDH) impeding access and engagement in FBT for diverse families (i.e., families belonging to identity groups subject to systemic barriers and prejudices). Methods Forty‐one FBT clinicians were recruited globally using purposive and snowball sampling. Clinicians participated in individual interviews or focus groups, discussing their experiences engaging diverse families in FBT. Qualitative data were transcribed verbatim and analyzed using reflexive thematic analysis. Results The findings underscore the pervasive impact of SDH on equitable access to FBT, specifically, the critical need for tailored approaches by clinicians to enhance access and engagement in FBT for diverse families experiencing practical, resource, and systemic barriers. Recommendations include broader dissemination of FBT knowledge, telehealth options to mitigate geographical barriers, community resource collaborations, and sensitivity to cultural and systemic factors impacting treatment engagement. Discussion Results of this study may inform future FBT planning (tailoring treatment approaches to address barriers), clinician training, clinical decision‐making tools, and opportunities for supporting under‐resourced families within the model, leading to more equitable FBT treatment access and engagement for diverse families.